Modeling of income inequality in the European Union countries - Ставицький, Андрій Володимирович; Козуб, М. (Київський національний університет імені Тараса Шевченка, 2019)
The article describes the current tendencies of the development of income differentiation processes in the countries of the European Union during the last 10 years. According to the analysis of the i mpact of income inequality on the economy of the countries, there is an inverse relationship between the growth of the gap between the income of different groups of people and the economic development. In order to confirm this conclusion and calculate the real index of income inequality, the dynamic stochastic general equilibrium (DSGE) model has been developed. The authors analysed three macroeconomics objects (household, firm, government), relationships between them and made their own model of eight equations. After that, the index of income inequality of all 27 current members of the European Union has been calculated for the last 10 years. The result shows in the general negative tendency. That is why it is important to choose the right strategic direction for the future development of the country. This DSGE model is a universal model and can be applied to other regions of the world after calibration of the parameters. The improvement of the model is about its expansion by adding other sources of income to get more accurate results. As a conclusion of the article, there was analysed the main directions of reforming the European economy in order to achieve sustainable development.

У статті розглянуто сучасні тенденції розвитку процесів диференціації доходів для країн Європейського Союзу за останні 10 років. Аналіз особливостей впливу нерівності доходів населення на економіку країн дав змогу зробити висновок про обернену залежність між зростанням розриву в доходах різних груп осіб та розвитком економіки. Для визначення результатів було розроблено динамічну стохастичну модель загальної рівноваги в умовах закритої економіки всіх 27 країн-дійсних членів Європейського Союзу за останні 10 років, де діють три макроекономічних суб'єкти: домогосподарство, фірма, держава. Обраховані показники відповідно до складеної моделі демонструють в загальному негативну тенденцію динаміки значення нерівності доходів, що зумовлює актуальність вибору стратегічного курсу розвитку країн із врахуванням таких тенденцій. Отримана модель є універсальною та може бути застосована для інших регіонів світу за умови попереднього калібрування параметрів, її розширення через введення додаткових джерел доходу з метою отримання більш точних результатів. Висновком дослідження став аналіз основних напрямів реформування європейської економіки для досягнення соціального прогресу країн.
Моделювання нерівності доходів у країнах Європейського Союзу
Keywords: нерівність доходів; диференціація населення; DSGE моделі; Європейський Союз; income inequality; population differentiation; DSGE model; European Union